2017
DOI: 10.1002/bit.26287
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial carbon metabolism: Fluxome plasticity and oxygen dependence

Abstract: Synechocystis sp. strain PCC 6803 has been widely used as a photo-biorefinery chassis. Based on its genome annotation, this species contains a complete TCA cycle, an Embden-Meyerhof-Parnas pathway (EMPP), an oxidative pentose phosphate pathway (OPPP), and an Entner-Doudoroff pathway (EDP). To evaluate how Synechocystis 6803 catabolizes glucose under heterotrophic conditions, we performed C metabolic flux analysis, metabolite pool size analysis, gene knockouts, and heterologous expressions. The results revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 42 publications
(68 reference statements)
8
61
0
Order By: Relevance
“…Our previous finding that deletion of the ED pathway (Deda) had the strongest effect on the ability to grow under photomixotrophic conditions was confirmed ( Figure 1B) (Chen et al, 2016). In darkness, i.e., under LAH and fermentative conditions, the OPP pathway (Dzwf, Dgnd) was most important ( Figure 1C and 1D), which is well in line with previous findings (Scanlan et al, 1995;Yang et al, 2002;Jansen et al, 2010;Wan et al, 2017). Deletion of the EMP pathway (Dpfk) led to diminished growth under LAH conditions but the effect was less severe than in Dzwf and Dgnd.…”
Section: Significance Of Distinct Glycolytic Routes Under Different Csupporting
confidence: 90%
See 2 more Smart Citations
“…Our previous finding that deletion of the ED pathway (Deda) had the strongest effect on the ability to grow under photomixotrophic conditions was confirmed ( Figure 1B) (Chen et al, 2016). In darkness, i.e., under LAH and fermentative conditions, the OPP pathway (Dzwf, Dgnd) was most important ( Figure 1C and 1D), which is well in line with previous findings (Scanlan et al, 1995;Yang et al, 2002;Jansen et al, 2010;Wan et al, 2017). Deletion of the EMP pathway (Dpfk) led to diminished growth under LAH conditions but the effect was less severe than in Dzwf and Dgnd.…”
Section: Significance Of Distinct Glycolytic Routes Under Different Csupporting
confidence: 90%
“…Deletion of the OPP pathway in cyanobacteria results in mutants that are unable to grow under light-activated heterotrophic (LAH) conditions (Scanlan et al, 1995;Jansen et al, 2010). This is well in line with flux analyses that found that glucose is predominantly metabolized by the OPP pathway in darkness (Yang et al, 2002;Wan et al, 2017). It has furthermore been reported that the PK pathway in cyanobacteria contributes to heterotrophic metabolism as well (Xiong et al, 2015).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Pool Size and Dynamic Labeling of Central Metabolites. The metabolic pool size (i.e., concentration of intracellular metabolites) of 34H was compared with that of E. coli during exponential growth at their respective normal-growth temperatures (4°C and 37°C) using the isotopic ratio method previously described (37). The analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic plasticity is also associated with the metabolic capabilities under various environmental growth conditions (e.g., photoautotrophic, photomixotrophic, or heterotrophic growth), 29,30 and this has been demonstrated through the rewiring of metabolic pathways for the production of 2,3-BDO. 12 Thus, the rewiring of metabolic pathways for directing carbon fluxes toward the desired products in cyanobacteria could facilitate the development of feasible S2C and S2F platforms.…”
Section: Introductionmentioning
confidence: 99%